Histopathological Features of Allergic Fungal Rhinosinusitis Provide Diagnostic and Therapeutic Insights - Shaalan Mofleh Hadeed; Karam Turath Tawfeeq (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Allergic Fungal Rhinosinusitis (AFRS) is a non-invasive subtype of fungal sinusitis marked by a hypersensitivity reaction to environmental fungi, predominantly Aspergillus. Specific Background: Its diagnosis depends on integrated clinical, radiologic, and histopathological assessments. Knowledge Gap: Despite established criteria, the histopathological profile of AFRS in Iraqi clinical settings remains underreported, limiting diagnostic precision. Aim: This study aimed to characterize the histopathological features of AFRS in patients managed at Al Salam Teaching Hospital, Mosul, Iraq, to improve diagnostic accuracy. Results: In a retrospective analysis of 42 cases from January 2023 to January 2024, all specimens demonstrated allergic mucin (100%), with 95.2% exhibiting dense eosinophilic infiltrates and 85.7% showing Charcot-Leyden crystals. Fungal hyphae, typically sparse, septate, and branching—consistent with Aspergillus—were detected in all samples using GMS and PAS stains. Novelty: This study highlights the consistent presence of Charcot-Leyden crystals in addition to the classical triad, emphasizing their diagnostic value in differentiating AFRS from other chronic rhinosinusitis forms. Implications: Recognition of these histopathological hallmarks is essential to guide treatment strategies focused on surgical and anti-inflammatory modalities, rather than systemic antifungal therapy. Highlight: Consistent Triad: Allergic mucin, eosinophils, and fungal hyphae are key diagnostic features. Diagnostic Marker: Charcot-Leyden crystals enhance specificity in AFRS detection. Therapeutic Focus: Emphasizes surgery and anti-inflammatory therapy over antifungals. Keywords: Allergic Fungal Rhinosinusitis, Histopathology, Charcot-Leyden Crystals, Eosinophilic Infiltrate, Aspergillus